2019
DOI: 10.2478/nuka-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fuel type on control rod reactivity of pebble-bed reactor

Abstract: As a crucial core physics parameter, the control rod reactivity has to be predicted for the control and safety of the reactor. This paper studies the control rod reactivity calculation of the pebble-bed reactor with three scenarios of UO 2 , (Th,U)O 2, and PuO 2 fuel type without any modifi cations in the confi guration of the reactor core. The reactor geometry of HTR-10 was selected for the reactor model. The entire calculation of control rod reactivity was done using the MCNP6 code with ENDF/B-VII library. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The structural components of the reactor core such as graphite reflectors were easily modeled while the coolant in the reflector side and especially, the reactor shutdown and control systems require special effort in modeling. The modeling and calculations performed in this study were demonstrated successfully in various publications [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Pebbles In Core Modelingmentioning
confidence: 76%
“…The structural components of the reactor core such as graphite reflectors were easily modeled while the coolant in the reflector side and especially, the reactor shutdown and control systems require special effort in modeling. The modeling and calculations performed in this study were demonstrated successfully in various publications [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Pebbles In Core Modelingmentioning
confidence: 76%
“…To obtain these values, a neutronic simulation was performed using the MCNP6.2 radiation transport code with the ENDF/B-VII.0 neutron cross-section library. MCNP is a well-established code for simulating the neutronic aspects of nuclear reactors and has been extensively used for various types of reactors [25][26][27][28][29][30]. Although MCNP may not be the most suitable simulation tool for MSR due to its decoupling from thermal-hydraulic calculations, it has nonetheless been used for simulating various MSR designs, such as MSBR [6,31,32], MSR-FUJI [9], TMSR-500 [33][34][35], and Integral Molten Salt Reactor (IMSR) [36], with good agreement to the reference.…”
Section: Methodsmentioning
confidence: 99%
“…Core com po nents and struc tures, such as ax ial and ra dial re flec tors, etc., were mod eled in a sim pler way. A de tailed de scrip tion of this pro ce dure was first in troduced by Lebenhaft [19] and found in sev eral pub li cations [20][21][22][23][24][25][26][27][28]. The whole fa cil ity mod el ing of HTR-Proteus is il lus trated in fig.…”
Section: Cal Cu La Tion Modelmentioning
confidence: 99%